PENGARUH PEMBERIAN EKSTRAK BAWANG PUTIH (Allium sativum Linn) TERHADAP ZONA HAMBAT PERTUMBUHAN BAKTERI Staphylococcus epidermidis secara in vitro - AKBAR DIOSASQIA PUTRA (Universitas Merdeka Madiun, 2019)
Background:Infectious diseases are the main cause of high morbidity and mortality rates, especially in developing countries such as Indonesia.Indonesia is abundant with plants that can be used as herbal medicine. Garlic is known as having antibacterial elements, one of them is for Staphylococcus epidermidisÂ which is one cause of dermal disease. This disease is often ignored in Indonesia because the price of the drug is not affordable by the community. So that garlic should be used as an alternative medicineObjective: This study aims to determine the antibacterial effect of garlic extract (Allium sativum L.) retarding the growth of Staphylococcus epidermidis.Methods: This study is experimental laboratory using plate diffusion method of